Euthanasia and assisted suicide in patients with personality disorders: a review of current practice and challenges - Mehlum, Lars; Schmahl, Christian; Berens, Ann; Doering, Stephan; Hutsebaut, Joost; Kaera, Andres; Kramer, Ueli; Moran, Paul Anthony; Renneberg, Babette; Ribaudi, Joaquim Soler; Simonsen, Sebastian; Swales, Michaela; et al. (Borderline personality disorder and emotion dysregulation, 2020)
Background Over the last two decades an increasing number of countries have legalized euthanasia and physician-assisted suicide (EAS) leading to considerable debate over the inherent ethical dilemmas. Increasing numbers of people with personality disorders, faced with unbearable suffering, have requested and received assistance in terminating their lives. EAS in people with personality disorders has, however, received very sparse attention from clinicians and researchers. In this paper, we examine the literature on the practice and prevalence of EAS in people with personality disorders to date and discuss the associated challenges for research and practice. Methods Narrative review of the literature combined with the authors’ collective experience and knowledge of personality disorders. Results In six of the eight countries where EAS is currently legal, mental disorders are accepted as disorders for which EAS may be granted. In four of these countries, EAS in minors with mental disorders is also accepted. Our literature search resulted in 9 papers on the subject of EAS in people with personality disorders. These studies suggest that most clinicians who grant EAS have indeed perceived their patients’ suffering as chronic, unbearable and untreatable without prospect of improvement. The majority of patients with personality disorders had tried some form of psychotherapy, but very few had received any of the relevant evidence-based treatments. The decision to grant EAS based on a perception of the patient’s illness as being untreatable with no prospect of improvement, could, thus, in many cases fail to meet the due care criteria listed in EAS laws. People with personality disorders more often wish for death for extended periods of time than people without these disorders. However, there is ample empirical data to show that suicidal tendencies and behaviour can be treated and that they fluctuate rapidly over time. Conclusions In light of our findings, we believe that the current legislation and practice of EAS for people with personality disorders is based on an inadequate understanding of underlying psychopathology and a lack of awareness about the contemporary treatment literature. Moreover, we assert that this practice neglects the individual’s potential for having a life worth living.